Crossing the Borders of Language and Culture: Samuel Beckett’s Waiting for Godot - Uchman, Jadwiga (Text Matters: A Journal of Literature, Theory and Culture, 2012)
The aim of the paper is to compare four versions of the text of Waiting for Godot: the French original, Beckett’s own translation into English and two Polish renderings done by Julian Rogoziński and Antoni Libera. The article starts with a short discussion concerning rules governing the translation process and then its evaluation. While working on the transposition of the French original into English, Beckett introduced numerous changes, this being due to his sensitivity to the very quality of each of the languages and specific references characteristic of the two cultures. Antoni Libera, an expert in Beckett’s oeuvre, argues that Beckett’s translations should be more adequately described as second language versions and that the artist recommended further translations based on his two language versions. Libera himself followed this recommendation while translating Beckett’s works into Polish. Upon publication, he provided illuminating notes, shedding light on the differences in Beckett’s versions and providing critical insight into the texts. Julian Rogoziński, on the other hand, based his translation of Waiting for Godot only on the French original. This accounts for the fact that, at times, his rendering of the text lacks precision and may not even be quite understandable. Rogoziński’s version is less satisfactory than that of Libera due to the fact that it was written earlier and by an older man, which at times results in the use of old-fashioned, outdated Polish diction and structures.